Our Palestine question: Israel and American Jewish dissent, 1948-1978 - Levin, Geoffrey (Yale University Press, 2023)
A new history of the American Jewish relationship with Israel focused on its most urgent and sensitive issue: the question of Palestinian rights American Jews began debating Palestinian rights issues even before Israel's founding in 1948. Geoffrey Levin recovers the voices of American Jews who, in the early decades of Israel's existence, called for an honest reckoning with the moral and political plight of Palestinians. These now-forgotten voices, which include an aid-worker-turned-academic with Palestinian Sephardic roots, a former Yiddish journalist, anti-Zionist Reform rabbis, and young left-wing Zionist activists, felt drawn to support Palestinian rights by their understanding of Jewish history, identity, and ethics. They sometimes worked with mainstream American Jewish leaders who feared that ignoring Palestinian rights could foster antisemitism, leading them to press Israeli officials for reform. But Israeli diplomats viewed any American Jewish interest in Palestinian affairs with deep suspicion, provoking a series of quiet confrontations that ultimately kept Palestinian rights off the American Jewish agenda up to the present era. In reconstructing this hidden history, Levin lays the groundwork for more forthright debates over Palestinian rights issues, American Jewish identity, and the U.S.-Israel relationship more broadly